Arterial Hypertension in Patients with Rheumatoid Arthritis. What should be known and considered at diagnosis and treatment? - N. M. Nikitina; T. A. Romanova; I. A. Afanas'ev; M. A. Tyapkina; A. P. Rebrov (Столичная издательская компания, 2016)
The risk of cardiovascular events in patients with rheumatoid arthritis (RA) is higher than this in population in 3.96 times. Arterial hypertension (HT) is one of the modifiable risk factors. According to published data 10-30% of patients have "masked" HT, detectable by the daily monitoring of blood pressure (BP). According to our own study, the prevalence of "masked" HT among RA patients is 28.2%. Among hypertensive patients with RA 7.5% of patients had resistant HT, 36.8% - do not regularly control BP. During daily monitoring of arterial stiffness in RA patients with HT we revealed that outpatient stiffness index was significantly higher than this in patients with essential hypertension (p<0.05). It is known that the basic anti-inflammatory drugs reduce cardiovascular risk; however, data regarding symptomatic treatment with nonsteroidal antiinflammatory drugs (NSAIDs) and glucocorticoids are contradictory. Antihypertensive treatment of HT patients with RA should be selected taking into account concomitant anti-inflammatory therapy. Treatment with calcium channel blockers is the most justified because they do not reduce their efficacy when used simultaneously with NSAIDs.